The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s12020-016-1128-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of BRAF mutation and SUVmax levels in thyroid cancer patients incidentally detected in 18F-fluorodeoxyglucose positron emission tomography

Abstract: The prognostic importance of F-fluorodeoxyglucose avidity in primary thyroid tumor and molecular basis responsible for its mechanism has not yet been well characterized. In this study, we aimed to evaluate the correlation between the maximum standardized uptake levels and B-type Raf kinase mutation positivity in incidentally detected papillary thyroid cancer patients duringF-fluorodeoxyglucose positron emission tomography examination. We retrospectively evaluated 6873 F-fluorodeoxyglucose-positron emission tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The afore-mentioned studies were cross-sectional so that any impact of incidentally identified diffuse uptake on subsequent thyroid dysfunction was unclear. Kim et al [41] did a cross-sectional and longitudinal study on 39,098 subjects undergoing comprehensive health examinations. At baseline, the prevalence of diffuse thyroidal FDG uptake was 1.6%.…”
Section: Patterns Of Fdg Uptake In the Thyroid Glandmentioning
confidence: 99%
“…The afore-mentioned studies were cross-sectional so that any impact of incidentally identified diffuse uptake on subsequent thyroid dysfunction was unclear. Kim et al [41] did a cross-sectional and longitudinal study on 39,098 subjects undergoing comprehensive health examinations. At baseline, the prevalence of diffuse thyroidal FDG uptake was 1.6%.…”
Section: Patterns Of Fdg Uptake In the Thyroid Glandmentioning
confidence: 99%